Advancements in the stability design of steel frames considering general non‐prismatic members: Extended Keynote of SDSS 2019. Issue 1 (18th February 2020) - White, Donald W.; Slein, Ryan; Toğay, Oğuzhan
Abstract: This paper discusses an innovative approach to the design of planar steel frames composed of prismatic and/or non‐prismatic members. The method evaluates the member stability limit states using an inelastic eigenvalue buckling analysis configured with column, beam and beam‐column inelastic stiffness reduction factors derived from the ANSI/AISC 360‐16 Specification. The resulting procedure provides a relatively rigorous evaluation of all member strength limits accounting for moment and axial force variations along the member lengths, non‐prismatic geometry effects, general out‐of‐plane bracing conditions and beneficial end restraint from less‐critical adjacent, unbraced segments and/or from end conditions. The approach uses a geometric non‐linear pre‐buckling analysis based on the AISC direct analysis method to estimate the in‐plane internal forces. Given these forces, an eigenvalue buckling solution is conducted to evaluate the overall member stability. Other limit states are addressed through cross‐section strength checks using the internal forces determined from the geometric non‐linear load‐displacement analysis. Calculations using this approach are compared with results from recent experimental tests.